Apakah Green Financing Mampu Menekan Risiko Kredit? Bukti Empiris pada Perbankan Indonesia - Reny Aziatul Pebriani; Vhika Meiriasari; Yunita Maharani (Jurnal Ilmiah Wahana Akuntansi, 2026)
This study aims to analyze the relationship between green financing and credit risk in the Indonesian banking sector. Credit risk is proxied by the Non-Performing Loan (NPL) ratio, while the research data were obtained from the financial statements and sustainability reports of Indonesian banks for the 2023–2025 period. This study employs a quantitative approach using descriptive statistics, classical assumption tests, simple linear regression, the coefficient of determination, and hypothesis testing. The results indicate that green financing has a negative and significant effect on credit risk. The regression equation obtained is NPL = 2.684 – 0.043 GF, indicating that an increase in green financing is associated with a decrease in the NPL ratio. The t-test produced a significance value of 0.013 (<0.05), indicating that the research hypothesis is accepted. The coefficient of determination (R² = 0.247) shows that green financing explains 24.7% of the variation in credit risk. These findings suggest that the implementation of green financing has the potential to improve financing quality, support effective credit risk management, and align with the principles of Maqāṣid al-Sharīʿah in promoting public welfare and environmental sustainability. Penelitian ini bertujuan menganalisis hubungan antara green financing dan risiko kredit pada perbankan Indonesia. Risiko kredit diproksikan menggunakan rasio Non-Performing Loan (NPL), sedangkan data penelitian diperoleh dari laporan keuangan dan laporan keberlanjutan perbankan periode 2023–2025. Penelitian menggunakan pendekatan kuantitatif dengan analisis statistik deskriptif, uji asumsi klasik, regresi linier sederhana, koefisien determinasi, dan uji hipotesis. Hasil penelitian menunjukkan bahwa green financing berpengaruh negatif dan signifikan terhadap risiko kredit. Persamaan regresi yang diperoleh adalah NPL = 2,684 – 0,043 GF, yang menunjukkan bahwa peningkatan green financing diikuti penurunan NPL. Uji t menghasilkan nilai signifikansi 0,013 (<0,05), sehingga hipotesis diterima. Nilai koefisien determinasi (R² = 0,247) menunjukkan bahwa green financing menjelaskan 24,7% variasi risiko kredit. Temuan ini mengindikasikan bahwa penerapan green financing berpotensi meningkatkan kualitas pembiayaan dan mendukung pengelolaan risiko kredit serta sejalan dengan prinsip maqāṣid al-sharīʿah dalam mewujudkan kemaslahatan dan keberlanjutan.